The Impact of Global Trends on Organization and Customer Satisfaction - Chin, Ming Hooi; Kee, Daisy Mui Hung; Kong, Rui Yang; Lee, Jia Ying; Yee, Jia Hui; Bhardwaj, Shelly; Chaudhary, Pratima; Pandey, Rudresh (Asia Pacific Journal of Management and Education (APJME), 2020)
The study aims to examine the impact of global trends on "MakeMyTrip" company as well as its customer satisfaction. The study has been done with the help of information provided on the company's websites, people's personal experiences, various hypotheses, and some statistical data. Surveys are also done to collect data from customers about their hospitality experiences and satisfaction. The findings and results which are based on the facts provided by customers and organization website suggested that the global trend does give a significant impact on organization and customer satisfaction. The study is aimed to provide ideas and solutions for organizations based on the impacts shown.